Czy literatura z kinematografią odsłaniają stereotypy narodowościowe Czechów i Polaków? Glosa konceptualnej analizy z zakresu domeny auto- i heterostereotypów = Does literature and the movies reveal ethnic stereotypes of the Czech and the Pole? A gloss on a conceptual analysis concerning auto- and heterostereotypes - Hampl, Lubomír (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author wishes to focus on how ethnonymic stereotypes of the Czech and the Pole are strengthened in literature and the movies (also in advertising, songs and within phraseological and idiomatic expressions). He focuses on the mass arts, where one can find issues related to cultural anthropology, linguistics and the historical and cultural realities, which belong to the sphere of humanities and social sciences.
Keywords: literature; cinematography; phraseology; idiomatic expressions; identity; stereotypes of Czech people; heterostereotypes of Polish people; cultural realities; literatura; kinematografia; frazeologia; stereotypy; idiom; Czechy; Polska